Description of the Yunnan shoot borer, Tomicus yunnanensis Kirkendall & Faccoli sp. n. (Curculionidae, Scolytinae), an unusually aggressive pine shoot beetle from southern China, with a key to the species of Tomicus - Kirkendall, Lawrence R.; Faccoli, Massimo; Ye, Hui (Zootaxa, 2008)
We describe a new and highly aggressive species of pine shoot beetle, Tomicus yunnanensis Kirkendall & Faccoli, which has been decimating Pinus yunnanensis forests in southwest China for almost three decades. This species was confused with T. piniperda until recent molecular studies showed the SW China populations to be quite divergent from T. piniperda of northeast China and Europe. The clearest morphological differences between these two species lie in the surface sculpture of the elytra: the new species has more widely spaced interstrial granules on the elytral disc, the punctures of interstria 2 on the declivity arranged irregularly and those of striae 1 and 3 smaller. The new species also has dense small hairs on the tip of the antennal club, while T. piniperda has only scattered small hairs on that segment. Mature T. piniperda specimens are uniformly black, while those of T. yunnanensis have the bulk of the elytra lighter than the base of the elytra and the pronotum. The new species is actually more similar to the Mediterranean species T. destruens, which differs in geographical distribution and in having the punctures of interstria 2 dense on the declivity and light-colored antennae. Species of Tomicus are of general concern to foresters because of their impact on conifer growth, but good illustrations for many species are lacking. We here provide a detailed key to all seven species of the genus (T. minor, T. piniperda, T. destruens, T. brevipilosus, T. yunnanensis and the virtually unknown T. puellus and T. pilifer) as well as diagnostic photographs and drawings. We summarize the biological differences between the new species and T. piniperda and recommend improved communication between taxonomists and forest entomologists, as avoidable taxonomic confusion such as that of T. yunnanensis and T. destruens with T. piniperda hinders the combatting of outbreaks of forest insects.